PENGARUH MEDIA SOSIAL, KUPON, PRODUK BUNDLING DAN DISKON YANG DILAKUKAN LOTTE GROSIR CIKARANG TERHADAP PRILAKU PEMBELIAN KONSUMEN - Andrianto Prasetya Nugroho; Sang Dewi Roro Basuki (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
This study aims to determine and analyze the influence of Social Media, Coupons, Bundling Products and Discounts conducted by Lotte Wholesale Cikarang on Consumer Purchase Behavior. To collect research data using a questionnaire. Sampling using non-probability sampling technique with purposive sampling method. The type of research used is quantitative. The population in this study are all Lotte Wholesale Cikarang consumers. The sample was determined with 125 respondents using the Malhotra formula. Based on the results of the research and discussion, it is concluded that Social Media, Bundling Products, and Discounts have a positive and significant effect on Consumer Purchase Behavior. While Coupons partially has a positive but has not significant effect on Consumer Purchase Behavior. The implications of this research that promotions by providing coupons are less desirable if they are given partially by Lotte Wholesale Cikarang consumers, but if you do Social Media promotions, product bundling coupons and discounts simultaneously can attract Lotte Wholesale Cikarang consumer buying behavior.